1999
DOI: 10.1111/j.1749-6632.1999.tb07671.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Matrix Metalloproteinases and Their Inhibition in Cutaneous Wound Healing and Allergic Contact Hypersensitivity

Abstract: Normal wounds can heal by secondary intention (epidermal migration to cover a denuded surface) or by approximation of the wound edges (e.g., suturing). In healing by secondary intention, epidermis-derived MMPs are important. Keratinocyte migration begins within 3-6 hr post injury, as basal cells detach from underlying basal lamina and encounter a dermal substratum rich in type I collagen. Cell contact with type I collagen in vitro stimulates collagenase-1 expression, which is mediated by the alpha 2 beta 1 int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
129
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(132 citation statements)
references
References 31 publications
(47 reference statements)
1
129
0
2
Order By: Relevance
“…MMP-2 is often made constitutively, but it is usually not activated unless conditions surrounding the cells change. In contrast, MMP-9 is not made constitutively, but its synthesis is induced in leukocytes, keratinocytes, monocytes, and macrophages as well as by various malignantly transformed cells (77). Stromelysin.…”
Section: Different Actions Of Mmpsmentioning
confidence: 99%
“…MMP-2 is often made constitutively, but it is usually not activated unless conditions surrounding the cells change. In contrast, MMP-9 is not made constitutively, but its synthesis is induced in leukocytes, keratinocytes, monocytes, and macrophages as well as by various malignantly transformed cells (77). Stromelysin.…”
Section: Different Actions Of Mmpsmentioning
confidence: 99%
“…Characteristic features of inflammatory skin diseases include dysregulation of pro-inflammatory mediators such as cytokines/chemokines, adhesion molecules, and enzymes, including matrix metalloproteinases (MMPs), which may accelerate migration of immune cells into the inflamed area of the skin (1)(2)(3). MMPs belong to the family of neutral endopeptidases, which participate in many physiological processes, including tissue remodeling and inflammation (Reviewed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…2f). The production of MMP1 by these control cells is likely to be due to the fact that the 'dermal' portion of the raft cultures was made of type I collagen and it has been shown that type I collagen stimulates production of MMP1 by keratinocytes in vitro and that MMP1 is necessary and sufficient for keratinocyte migration over type I collagen (Pilcher et al, 1999).HaCaT-16E5 cells were positive for both MMP9 and MMP1 both in the basal layer and in the invading pockets (Fig. 3k, l).…”
mentioning
confidence: 99%